The lineman's and cableman's handbook - Shoemaker, Thomas M. 1921- (McGraw-Hill, 2007)
Covering both overhead and underground electrical transmission and distribution, this reference graphically lays out the basic principles, equipment, standards, and safety regulations, allowing electrical workers to avoid costly errors, diagnose and repair power failures, and ensure optimum safety.